CHIME ages of xenotime, monazite and zircon from beryllium pegmatites in the Napier Complex, Khmara Bay, Enderby Land, East Antarctica - Grew, Edward S.; Suzuki, Kazuhiro; Asami, Masao (National Institute of Polar Research, 2001)
P(論文) Dating by the chemical Th-U-total Pb isochron method (CHIME) was carried out on xenotime, monazite and zircon from beryllium pegmatites intruded at about 2500 Ma in the ultrahigh-temperature metamorphic Napier Complex. No meaningful results were obtained on zircon from an associated Be-free pegmatite. All analyzed mineral grains are chronologically heterogeneous, and apparent ages range from -2460 Ma to 550 Ma with conspicuous concentration at 2200, 1700 and 700 Ma. The 2168±36 Ma age for the chronologically homogeneous, non-metamict core of a large xenotime grain dates intense post-emplacement deformation and metamorphism, possibly the granulite-facies event M-2 proposed by E.S. Grew et al. (Polar Geosci., 13, 1, 2000) to explain the breakdown of sapphirine and quartz to sillimanite, surinamite, orthopyroxene and/or garnet in the pegmatites and their host rocks. CHIME ages near ～1700 Ma and ～700 Ma could result from incomplete resetting by amphibolite-facies events (M-3, -4) between ～1100 and ～500 Ma. In general, the minerals appeared to have experienced no significant new growth during the later events, so that the effect of these events is expressed in the U-Th-Pb system in the original mineral. Because most of the ages were obtained on non-metamict portions of the analyzed grains, we doubt that metamictization can be the cause of most of the observed chronological heterogeneity. The lack of evidence for the ～2500 Ma emplacement age in the CHIME data could be due to the reliance on total concentrations of Th, U and Pb, which may be more affected by subsequent deformation and metamorphism than the isotope ratios measured in conventional U-Pb dating. departmental bulletin paper